Potret Madrasah di Dunia Islam: Keragaman, Kompleksitas, dan Persaingan Konsep Keislaman - Subhan, Arief (Studia Islamika, 2007)
Book Review: Robert w. Hefner and Muhammad Qasim Zaman, schooling Islam: The culture and Politics of Modem Muslim Education (Princeton: Princeton University Press, 2007).This book offers a portrait of Islamic education while presenting their struggles with s variety of political systems, modernization, and religious ideology. Cases were studied in important regions in the lslamic world such as Turkey, Egypt, Pakistan, Indonesia, Morocco, and Mali as well as Islamic education in the West, in this case, England. In the discussion is revealed that the Islamic educational institutions, especially the madrasah are not only confronted by changing social and political realities, but also by the issue: How to make a modern Muslim. In response to these challenges various models of Islamic education appeared in various regions in the Muslim world.DOI: 10.15408/sdi.v14i3.551